Surgical outcomes after laparoscopic or robotic liver resection in hepatocellular carcinoma: a propensity‐score matched analysis with conventional open liver resection. Issue 4 (4th November 2015) - Han, Dai Hoon; Choi, Sung Hoon; Park, Eun Jung; Kang, Dae Ryong; Choi, Gi Hong; Choi, Jin Sub
Abstract: Background: This study was designed to compare perioperative and oncologic outcomes between minimally invasive liver resection (MILR) and conventional open liver resection (COLR) for hepatocellular carcinoma (HCC) using a propensity‐score matched analysis. Methods: Ninety‐nine patients who received MILR were matched with 198 patients treated with COLR out of 928 patients with HCC who received curative liver resection from 2002 to 2012. A multivariable logistic model based on factors related to the patient, tumor, and surgical procedure was used to estimate a propensity score. Results: The MILR group experienced significantly less intraoperative blood loss (mean: 389.55 vs 580.66 mL; P = 0.008), lower complication rates (13.1% vs 24.7%; P = 0.020), and a shorter length of hospital stay (mean: 8.40 vs 13.39 days; P < 0.001). The two groups did not differ significantly in disease‐free ( P = 0.701) or overall survival ( P = 0.086). Conclusions: MILR produced better perioperative and comparable oncologic outcomes than COLR for HCC. Copyright © 2015 John Wiley & Sons, Ltd.